Code Smells and Refactorings for Elixir - Vegi, Lucas Francisco da Matta; Valente, Marco Tulio (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft), 2025)
Elixir is a modern functional language gaining traction in the industry, but the internal quality of the code written with this language still lacks research. To fill this gap, this thesis investigates code smells and refactorings specific to Elixir, drawing inspiration from classic Fowler catalogs. In the first two studies, a mixed-method approach was adopted to catalog 35 code smells (23 novel and 12 traditional), validated by 181 developers, and 82 refactorings (14 novel), validated by 151 developers. In the third study, we correlated code smells and refactorings, establishing practical guidelines for the disciplined removal of smells through refactorings. The results impact both the prevention of code smells and the prioritization of refactorings in Elixir, for instance.